Pengamanan Audio Menggunakan Metode RSA dan Steganografi Spread spectrum Berbasis Android (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Audio is a multimedia element whose function is the same as text, video or images, but for the recipient it can only be heard through human hearing, which is 20 to 20,000 Hz. Audio can also be in the form of a song that is often listened to and has a high selling power, therefore audio is also often traded or rented. In this study, the application was developed using the Spread spectrum method, Rivest Shamir Adleman and assisted also by the Standard Advanced Encryption method to secure audio to protect against data theft by unauthorized parties. This application is based on Android which can be further developed to run more flexibly and make it easier for users to use it. From the test results the application can process input and output as expected. For testing the results of image quality, which is an audio password insertion container, in this test, the PSNR value with an average of 56,851 is obtained, and the MSE value with an average value of 0.124 which is a good result for testing image quality.